Trace relations in deformed gauge theories - Madhusudhan Raman; Aditi Shahani (Journal of High Energy Physics)
Abstract We compute trace relations governing chiral ring elements of fully Ω-deformed N $$ \mathcal{N} $$ = 2⋆ gauge theories with SU(N) gauge groups by demanding the regularity of the fundamental qq-character.